The affinity of Archean crust on the Yilgarn-Albany-Fraser Orogen boundary: Implications for gold mineralisation in the Tropicana Zone - Kirkland, Chris; Spaggiari, C.; Smithies, R.; Wingate, M.; Belousova, E.; Gréau, Y.; Sweetapple, M.; Watkins, R.; Tessalina, Svetlana; Creaser, R. (Elsevier, 2015)
Craton margins can be subject to a wide array of gold genesis and redistribution processes, although high-grade terrains on craton margins are frequently viewed as less prospective than lower-grade counterparts. In contrast to this, the high-grade Tropicana Zone, a newly defined Archean crustal component on the eastern margin of the Yilgarn Craton within the Albany–Fraser Orogen (AFO), contains a significant Proterozoic gold deposit. This deposit and zone comprise mid-amphibolite to granulite-facies gneissic rocks with evidence of partial melting and granite injection. The Tropicana Zone contains significant low-Si, LILE-enriched, granites classed as sanukitoids. Along with the distinctive compositions, the rarity of these rocks within any Archean craton suggests that the granitoid protoliths represent a single suite, emplaced during one event.Due to the intense granulite-facies overprinting of the Tropicana Zone rocks, determination of the magmatic protolith age for these sanukitoids is challenging. Nonetheless, the best age estimate for magmatism is 2692 ± 16 Ma, based on the youngest zircons preserving textural evidence of growth within a viscous silicate melt. This age is older than compositionally similar magmatism found within the Yilgarn Craton, although a sanukitoid in the Northern Foreland of the AFO has a similar age. Furthermore, the granulite-facies metamorphic zircon growth in the Tropicana Zone at 2718–2554 Ma was prolonged compared to that in the Yilgarn Craton. Nonetheless, the Hf isotopic signature of the Tropicana Zone zircon shares strong similarity to that from the Eastern Goldfields Superterrane of the Yilgarn Craton. This implies that the Tropicana Zone reflects a deeper crustal level of the Yilgarn Craton, exhumed and thrust NW an unknown distance over the craton edge. In addition, we observe that the granulite-facies zircons have a less radiogenic Hf-isotope signature than the preserved pre-metamorphic zircon cores. Based on correlations with alpha dose, U and Th content and 176Hf/177Hf we suggest this reflects the preferential destruction and release of unradiogenic Hf from inherited zircon whereas the protolith sanukitoid zircon, with lower U and Th content, was more resistant to mobilisation during high-grade metamorphism. We note this situation may be a more general response of the Hf isotopic system, in which zircon grown in a more mafic melt is less likely to contribute to the metamorphic Hf reservoir than its felsic counterpart.Juvenile granitic veins dated at c. 1780 Ma intruded into the Tropicana Zone indicate that the Tropicana Zone was structurally emplaced at or before c. 1780 Ma, given similar Proterozoic magmatic events are well documented from (para)autochthonous adjacent units. Re–Os dating of pyrite coeval with one generation of gold in these rocks indicates model ages of c. 2100 Ma, supportive of a Palaeoproterozoic age of mineralisation. This mineralisation event is distinct from major Proterozoic tectonothermal events elsewhere in the AFO. Sanukitoid magmas are well-known for gold fertility and were likely the original source of gold in the Tropicana Zone, which was subsequently concentrated into brittle structures during several episodes. Gold mineralisation post-dated peak metamorphic conditions and is significantly younger than gold mineralisation within other parts of the adjoining Yilgarn Craton.